Pengaruh Jenis dan Konsentrasi Bahan Penstabil terhadap Karakteristik Fisikokimia dan Sensori Ready to Drink Parijoto - Handayani, Isti; Septiana, Aisyah Tri; Salsabila, Muna Verentsya (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
Parijoto (Medinilla speciosa), a native Indonesian fruit with potential health benefits, has limited utilization due to its short shelf life, firm texture, and sour taste. Processing parijoto into a ready to drink (RTD) beverage is a potential strategy to improve its usability and product value. However, the stability of fruit juice beverages depends on maintaining a homogeneous mixture of juice, water, and other ingredients; therefore, stabilizers are required to ensure product quality. This study aimed to evaluate the effects of stabilizer type and concentration on the physicochemical and sensory characteristics of parijoto RTD beverages. A factorial completely randomized design (CRD) was applied with two factors: stabilizer type (carboxymethyl cellulose/CMC, pectin, and a CMC–pectin mixture) and stabilizer concentration (0.25, 0.50, and 0.75%). Physical characteristics analyzed included viscosity, while chemical parameters consisted of pH, total soluble solids, and reducing sugars. Sensory evaluation was conducted using a preference test. The results showed that stabilizer type and concentration significantly affected viscosity, pH, and total soluble solids of the RTD beverage (p